Measurement of the flavour-specific CP-violating asymmetry $a_{\rm sl}^s$ in $B_s^0$ decays - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2013)
The CP-violating asymmetry a_{sl}^s is studied using semileptonic decays of Bs and anti-Bs mesons produced in pp collisions at a centre-of-mass energy of 7 TeV at the LHC, exploiting a data sample corresponding to an integrated luminosity of 1.0/fb. The reconstructed final states are Ds^(+/-)μ ^(-/+), with the Ds^(+/-) particle decaying in the φπ^(+/-) mode. The Ds^(+/-)μ ^{-/+) yields are summed over Bs and anti-Bs initial states, and integrated with respect to decay time. Data-driven methods are used to measure efficiency ratios. We obtain $a_{sl}^s$ = (-0.06 +/- 0.50 +/- 0.36)%, where the first uncertainty is statistical and the second systematic.